Amino acid composition, antioxidant activity and mineral content of Achatina fulica snail slimes and edible bird’s nest - Dang Tin Tin; Ong Mei Kying; Wong Seng Mei; Ong Ching Ang (BIO Web of Conferences)
This study was performed to investigate whether the snail slimes which also well-known for their anti-aging properties, can be served as an alternative for edible bird’s nest (EBN) in our daily lives. The amino acid composition of samples was evaluated using a reversed-phase High Performance Liquid Chromatography. The four major amino acids detected in snail slimes were aspartic acid (3.80 µmol/mL), glutamic acid (2.87 µmol/mL), alanine (2.23 µmol/mL) and serine (1.80 µmol/mL), while for EBN, the top four amino acids were proline (5.31 µmol/mL), serine (5.27 µmol/mL), aspartic acid (4.78 µmol/mL) and threonine (3.97 µmol/mL). In overall, EBN possessed significantly (p < 0.05) higher total amino acid content (42.63 µmol/mL) than the snail slimes (23.59 µmol/mL). Besides, the EBN was found to have significantly higher (p < 0.05) DPPH free radical scavenging activity (25.12 %) as compared to the snail slimes (16.02 %). The four major elements identified in snail slimes and EBN were sodium, calcium, potassium and magnesium. Snail slimes contained higher levels of minerals compared to EBN. In conclusion, the snail slimes can potentially be served as an alternative of EBN to those people suffered from mineral deficiencies.